Beneficial neurocognitive effects of chronic naltrexone treatment in rats poisoned with the sarin analog diisopropylfluorophosphate - Martin, Justin Riley (East Carolina University, 2019)
Accidental poisoning with organopesticides utilized for agricultural purposes is commonly seen in rural communities, including many areas of eastern NC. It is documented that chronic nerve damage, including cerebral dysfunction and neuropsychological disabilities occur in humans after such poisonings. Unfortunately, organophosphate compounds are also used as nerve agents in chemical warfare and terrorist attacks. Some of the symptoms that persist after exposure include headaches, memory loss, confusion, and fatigue. Studies have shown acute poisonings can induce impairments on performance in neuropsychological tests. While acute physiological manifestations are well managed with atropine and pralidoxime, a large percentage of subjects eventually develop neurocognitive problems that include memory loss, confusion, anxiety disorders and increased aggression. An explanation is that an inflammatory cycle within the CNS may be a common mechanism of many neurological conditions. This suggests that novel, anti-inflammatory drugs may be beneficial in minimizing the impact of inflammatory processes, thus reducing the onset of neuropsychological impairments. Naltrexone is a potent, anti-inflammatory agent that is safe and readily available. Indeed, clinical trials have shown that naltrexone is effective in several inflammation-related diseases, such as neurogenic pain or movement disorders. This study involved a rodent model of acute organophosphate poisoning using diisopropylfluorophosphate (DFP), an irreversible acetylcholinesterase inhibitor, to determine if naltrexone can mitigate the development of neurocognitive problems in the weeks after exposure. Adult rats were given acute DFP (5 mg/kg) + saline, DFP + naltrexone (5 mg/kg), or naltrexone; rats were treated chronically with naltrexone for 12 weeks. Afterwards, they underwent neurocognitive assessment for associative learning deficits using trace eyeblink classical conditioning (TECC). This task is mediated by an intact hippocampus, which may be vulnerable to DFP. Results indicate that rats poisoned with DFP but treated with naltrexone show improvements in conditioned responding in TECC. Naltrexone has been shown to be neuroprotective against inflammation-mediated neurodegeneration and is therefore a good candidate in examining the prevention of neurological sequela from organophosphate poisoning.
Keywords: Diisopropylfluorophosphate